Strategi Guru dalam Menumbuhkan Karakter Disiplin Belajar Siswa Kelas V di SDN Kamal 1 Bangkalan Madura - Ridha Rahmah Cahyani; Laily Mar’atul Maghfiroh; Rika Wulandari (ARZUSIN, 2025)
Low learning discipline among elementary school students, particularly fifth-grade students at SDN Kamal 1, has a significant impact on the effectiveness of instruction, as reflected in behaviors such as arriving late to class, lack of focus during lessons, non-compliance with rules, and low commitment to completing assignments. This study aimed to describe teachers’ strategies in fostering students’ learning discipline, identify the challenges faced, and explain the solutions implemented in the learning process. A descriptive qualitative method with a case study design was employed, with the fifth-grade classroom teacher selected through purposive sampling as the main subject. Data were collected through in-depth interviews, classroom observations, and documentation, and were analyzed using the Miles and Huberman model, which comprises data reduction, data display, and conclusion drawing. The findings indicate that three main strategies—habituation, role modeling, and positive reinforcement—play an effective role in shaping students’ learning discipline, although their implementation remains constrained by low discipline habits in the home environment and limited student self-awareness. These results reinforce character education theory that emphasizes the importance of value internalization through continuous habituation and reinforcement, and they affirm that the success of discipline formation does not depend solely on teacher strategies but also requires support from the family environment and the broader school ecosystem. The study implies the need for more intensive collaboration between teachers and parents, strengthening of habituation programs at school, and the development of learning strategies that are more responsive to students’ characteristics and needs.